The role of Toll-like receptor signaling pathways in cerebrovascular disorders: the impact of spreading depolarization - Ashayeri Ahmadabad, Rezan (J Neuroinflammation, 2020)
Cerebral vascular diseases (CVDs) are a group of disorders that affect the blood supply to the brain and lead to the reduction of oxygen and glucose supply to the neurons and the supporting cells. Spreading depolarization (SD), a propagating wave of neuroglial depolarization, occurs in different CVDs. A growing amount of evidence suggests that the inflammatory responses following hypoxic-ischemic insults and after SD plays a double-edged role in brain tissue injury and clinical outcome; a beneficial effect in the acute phase and a destructive role in the late phase. Toll-like receptors (TLRs) play a crucial role in the activation of inflammatory cascades and subsequent neuroprotective or harmful effects after CVDs and SD. Here, we review current data regarding the pathophysiological role of TLR signaling pathways in different CVDs and discuss the role of SD in the potentiation of the inflammatory cascade in CVDs through the modulation of TLRs.